Determination of the Frictional Properties of Titanium and Nickel Alloys Using the Digital Image Correlation Method - Kartal, M; Mulvihill, D; Nowell, D; Hills, D (2011)
The paper describes experiments to investigate the frictional properties of a Titanium alloy (Ti-6Al-4V) and a Nickel alloy (Udimet 720) under representative engineering conditions. Flat fretting pads with rounded corners were clamped against a flat specimen and a servo-hydraulic tensile testing machine was used to apply cyclic displacement to the specimen. Slip displacement between the specimen and pad was measured remotely using an LVDT and locally using digital image correlation. The latter approach allowed accurate determination of the tangential contact stiffness from frictional hysteresis loops. The results obtained show that the contacts are significantly less stiff than would be predicted by a smooth elastic contact analysis. A finite element model of the experimental contact geometry was constructed and it was shown that good agreement with the experimental measurements of contact stiffness can be obtained with a suitable choice of elastic modulus for a compliant surface layer. © 2010 Society for Experimental Mechanics.